A novel glucagon‐like peptide 1/glucagon receptor dual agonist improves steatohepatitis and liver regeneration in mice. Issue 3 (30th January 2017) - Valdecantos, M. Pilar; Pardo, Virginia; Ruiz, Laura; Castro‐Sánchez, Luis; Lanzón, Borja; Fernández‐Millán, Elisa; García‐Monzón, Carmelo; Arroba, Ana I.; González‐Rodríguez, Águeda; Escrivá, Fernando; Álvarez, Carmen; Rupérez, Francisco J.; et al.
Abstract : Because nonalcoholic steatohepatitis (NASH) is associated with impaired liver regeneration, we investigated the effects of G49, a dual glucagon‐like peptide‐1/glucagon receptor agonist, on NASH and hepatic regeneration. C57Bl/6 mice fed chow or a methionine and choline–deficient (MCD) diet for 1 week were divided into 4 groups: control (chow diet), MCD diet, chow diet plus G49, and M+G49 (MCD diet plus G49). Mice fed a high‐fat diet (HFD) for 10 weeks were divided into groups: HFD and H+G49 (HFD plus G49). Following 2 (MCD groups) or 3 (HFD groups) weeks of treatment with G49, partial hepatectomy (PH) was performed, and all mice were maintained on the same treatment schedule for 2 additional weeks. Analysis of liver function, hepatic regeneration, and comprehensive genomic and metabolic profiling were conducted. NASH was ameliorated in the M+G49 group, manifested by reduced inflammation, steatosis, oxidative stress, and apoptosis and increased mitochondrial biogenesis. G49 treatment was also associated with replenishment of intrahepatic glucose due to enhanced gluconeogenesis and reduced glucose use through the pentose phosphate cycle and oxidative metabolism. Following PH, G49 treatment increased survival, restored the cytokine‐mediated priming phase, and enhanced the proliferative capacity and hepatic regeneration ratio in mice on the MCD diet. NASH markers remained decreased in M+G49 mice after PH, and glucose use was shifted to the pentose phosphate cycle and oxidative metabolism. G49 administered immediately after PH was also effective at alleviating the pathological changes induced by the MCD diet. Benefits in terms of liver regeneration were also found in mice fed HFD and treated with G49. Conclusion : Dual‐acting glucagon‐like peptide‐1/glucagon receptor agonists such as G49 represent a novel therapeutic approach for patients with NASH and particularly those requiring PH. (Hepatology 2017;65:950‐968).